Letter - Pontefract Central Strike Committee, 6 May 1926 (page 1) (Pontefract)
1926-05-06 "Letter - Pontefract Central Strike Committee, 6 May 1926 (page 1)" [g0103001.jpg], 6 May 1926, Pontefract Central Strike Committee Local Organisation